Peningkatan Keterampilan Membaca Permulaan Menggunakan Metode Scramble Siswa Kelas III Sekolah Dasar Muara Bungo - Halijah, Halijah; Guswita, Reni; Hidayat, Puput Wahyu (CV. Master Literasi Indonesia, 2025)
This study began with the background and initial reading skills, only 16 students were fluent in reading with a score of 68%. This indicates that the reading results have not met the KKTP set bg the school, which is 70. The purpose of this study wes to describe the improvement of initial reading skills using the Scrambel 100/IIMuara Bungo. The research method used is Classroom Action Research. The research subjects were 28 students of class II of SDN 100/II Muara Bungo. Data collection used wa observation and testing. The data collection instrument used an observation sheet instrument and test data using a test sheet instrument. The observation data analysis technique used data reduction analysis techniques, data dispay and conclusion drawing verification. The results of the study showed the using the Scramble ethod can improve early reading skills. 1) The results of teacher observations in cycle I, meeting I, were 85% and meeting II 95%, cycle II increased to meeting I, namely 95% and meeting II, 95%. The results of student observations in cycle I, meeting I were 64% and meeting II, 82%, cycle II increased to meeting I, namely 89% and meeting II 96%. 2) The results of the initial reading test in cycle I were 75% and cycle II increased to 92%. It can beconcluded thet using the Scramble method can improve early reading skills in grede III.